ETIKA PESERTA DIDIK DAN PENDIDIK DI MADRASAH ALIYAH MATHOLI'UL HUDA TROSO JEPARA - Rohmah Fatmah; Ana Rahmawati (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2023)
The results showed that the ethics of students in madrasas varied, one class must have one or two students who lacked ethics, while the ethics of teachers in madrasas were very good. , although there are a few who lack or have not mastered. The teacher's attitude towards students who lack ethics is reprimanded, asked gently and approached, or usually given physical punishment, such as sweeping, reciting the Koran and mopping, not physical punishment by playing with hands. The attitude of students towards teachers who lack ethics, some are just silent and some are reprimanded if they dare. The method of teaching for students who have ethics and students who do not have ethics is the same, there is no difference, if there are students who lack ethics they are only reprimanded. There is a difference between teachers who have ethics and teachers who lack ethics, teachers who have ethics will not discriminate between their students, such as distinguishing the abilities of their students and vice versa, teachers who lack ethics will discriminate between their students.